Identifying educator behaviours for high quality verbal feedback in health professions education: literature review and expert refinement. Issue 1 (December 2016) - Johnson, Christina; Keating, Jennifer; Boud, David; Dalton, Megan; Kiegaldie, Debra; Hay, Margaret; McGrath, Barry; McKenzie, Wendy; Nair, Kichu; Nestel, Debra; Palermo, Claire; Molloy, Elizabeth
Abstract Background Health professions education is characterised by work-based learning and relies on effective verbal feedback. However the literature reports problems in feedback practice, including lack of both learner engagement and explicit strategies for improving performance. It is not clear what constitutes high quality, learner-centred feedback or how educators can promote it. We hoped to enhance feedback in clinical practice by distinguishing the elements of an educator's role in feedback considered to influence learner outcomes, then develop descriptions of observable educator behaviours that exemplify them. Methods An extensive literature review was conducted to identify i) information substantiating specific components of an educator's role in feedback asserted to have an important influence on learner outcomes and ii) verbal feedback instruments in health professions education, that may describe important educator activities in effective feedback. This information was used to construct a list of elements thought to be important in effective feedback. Based on these elements, descriptions of observable educator behaviours that represent effective feedback were developed and refined during three rounds of a Delphi process and a face-to-face meeting with experts across the health professions and education. Results The review identified more than 170 relevant articles (involving health professions, education, psychology and business literature) and ten verbal feedback instruments in health professions education (plus modified versions). Eighteen distinct elements of an educator's role in effective feedback were delineated. Twenty five descriptions of educator behaviours that align with the elements were ratified by the expert panel. Conclusions This research clarifies the distinct elements of an educator's role in feedback considered to enhance learner outcomes. The corresponding set of observable educator behaviours aim to describe how an educator could engage, motivate and enable a learner to improve. This creates the foundation for developing a method to systematically evaluate the impact of verbal feedback on learner performance.